MODELLING RIVER DISCHARGE AND PRECIPITATION FROM ESTUARINE SALINITY IN THE NORTHERN CHESAPEAKE BAY: APPLICATION TO HOLOCENE PALAEOCLIMATE - Saenger C.; Cronin T.; Thunell R.; Vann Ch. (My University, 2006)
Long-term chronologies of precipitation can provide a baseline against which twentieth-century trends in rainfall can be evaluated in terms of natural variability and anthropogenic influence. However, there are relatively few methods to quantitatively reconstruct palaeoprecipitation and river discharge compared with proxies of other climatic factors, such as temperature. We developed autoregressive and least squares statistical models relating Chesapeake Bay salinity to river discharge and regional precipitation records. Salinity in northern and central parts of the modern Chesapeake Bay is influenced largely by seasonal, interannual and decadal variations in Susquehanna River discharge, which in turn are controlled by regional precipitation patterns. A power regressive discharge model and linear precipitation model exhibit well-defined decadal variations in peak discharge and precipitation. The utility of the models was tested by estimating Holocene palaeoprecipitation and Susquehanna River palaeodischarge, as indicated by isotopically derived palaeosalinity reconstructions from Chesapeake Bay sediment cores. Model results indicate that the early-mid Holocene (7055-5900 yr BP) was drier than the late Holocene (1500 yr BP-present), the ’Mediaeval Warm Period’ (MWP) (1200-600 yr BP) was drier than the ’Little Ice Age’ (LIA) (500-100 yr BP), and the twentieth century experienced extremes in precipitation possibly associated with changes in ocean-atmosphere teleconnections.
Keywords: CHESAPEAKE BAY; PALAEOCLIMATE; PALAEOPRECIPITATION; PALAEOHYDROLOGY; SALINITY; SUSQUEHANNA; RIVER; TELECONNECTIONS; HOLOCENE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен